Uji Regresi Linier Sederhana Dan Regresi Ganda - Zulkifli Zulkifli (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2026)
This study aims to analyze the application of simple linear regression and multiple regression in determining the relationship between independent variables and dependent variables. The research method used is quantitative analysis with statistical testing through regression analysis techniques. The data used in this study were obtained from observations and documentation related to the research variables. Simple linear regression is used to determine the effect of one independent variable on the dependent variable, while multiple regression is used to determine the simultaneous effect of two or more independent variables. The results show that the independent variables have a significant effect on the dependent variable, both partially and simultaneously. The coefficient of determination indicates that the regression model is able to explain the relationship between variables effectively. Thus, regression analysis can be used as an analytical tool in predicting and understanding the influence between variables in research